The Development of Interactive E-Book-Based Teaching Materials for Senior High School Students - Haniah, Haniah; Mahira, Mahira; Djuaeni, Muh. Napis (Institut Agama Islam Negeri Curup, 2023)
This study aimed to develop interactive e-book-based teaching materials for Madrasah Aliyah students in class X to support independent learning and to assess the levels of validity and practicability of their use. The growth of students' learning is positively impacted by the creation of teaching materials that are appropriate for their circumstances and ages, especially those that encourage independent learning. Field evidence indicates that students must build their knowledge outside the classroom to learn effectively, as suggested by the constructivist theory. This research employed the research and development method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The data were collected through questionnaires and observations and then analyzed using descriptive statistical techniques. The product of this research was an interactive e-book assisted by a Heyzine Flipbook with al-tahiyyat wa al-ta’aruf materials that could be accessed online via smartphones, tablets, and laptops. Based on the validation conducted by media experts, material specialists, and Arabic linguists, the validity of this product was rated as legitimate and worth testing with a feasibility score of 4.42, which was good, and an average eligibility percentage of 88%. Responses from 40 students and five Arabic teachers, who had a very positive response rate of 91%, were used to determine the practical value of use. Based on these results, the interactive e-book-based teaching materials assisted by the Heyzine Flipbook al-tahiyyat wa al-ta’aruf materials for Madrasah Aliyah students were valid and practical for use.